2013
DOI: 10.1590/s1806-37132013000500006
|View full text |Cite
|
Sign up to set email alerts
|

The influence of leptin on Th1/Th2 balance in obese children with asthma

Abstract: Objective: In individuals with asthma, obesity induces the production of leptin and is associated with disease severity. Our objective was to evaluate the levels of serum leptin and their effect on Th1/Th2 balance in obese and non-obese children with asthma, as well as to investigate the association between serum leptin levels and clinical outcomes. Methods: We evaluated 50 atopic children with physician-diagnosed moderate-to-severe persistent asthma and 20 controls. The children with asthma were divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 26 publications
6
19
0
3
Order By: Relevance
“…The association with weight is in line with results from univariate analysis from healthy adults, reported by Jo et al . This could in theory be explained by Th1‐polarisation and lower levels of Th2‐cytokines seen in obese patients with asthma that could lead to lower FeNO levels. However, this relation became statistically non‐significant after adjustments in the present study, and it was mainly explained by gender differences in the report of Jo et al .…”
Section: Discussionsupporting
confidence: 90%
“…The association with weight is in line with results from univariate analysis from healthy adults, reported by Jo et al . This could in theory be explained by Th1‐polarisation and lower levels of Th2‐cytokines seen in obese patients with asthma that could lead to lower FeNO levels. However, this relation became statistically non‐significant after adjustments in the present study, and it was mainly explained by gender differences in the report of Jo et al .…”
Section: Discussionsupporting
confidence: 90%
“…In a previous study, leptin levels in obese and non-obese asthmatic children were higher than in matched non-asthmatic controls. Nevertheless, elevated leptin values in the same study were positively correlated with high levels of interferon (INF)-g (Th1 cytokine) that were attributed to inflammation around the bronchioles and the aggravation of severe asthma [22]. Ghrelin is expected to have anti-inflammatory actions that might suppress proinflammatory cytokines such as tumor necrosis factor (TNF)-α, IL-1β and IL-6, which are involved in the inflammation and pathogenesis of asthma [25,26].…”
Section: Discussionmentioning
confidence: 83%
“…In accordance with the guidelines of The Saudi Initiative for Asthma [20] and the Global Initiative for Asthma [21], asthma was diagnosed based on a history of recurrent or chronic chest symptoms such as coughing, wheezing, difficulty breathing, and chest tightness that demonstrated clinical reversibility with short-acting bronchodilator treatment. Symptom score in children with asthma was assessed according to a six-domain asthma symptom score that includes dyspnea, tightness in the chest, wheezing during the day, wheezing during the night, and daily performance [22].…”
Section: Study Design and Settingmentioning
confidence: 99%
“…The concentration of IL-4 were lower in both groups suggesting that leptin plays role on supressing the Th2 cell cytokine production of IL-4. 21 Zinc supplementation associated with decreased level of IL-4 concentration on both group but more pronounced in supplementation group suggesting that zinc supplementation decrease the risk of allergy. Study by Tascilar on 34 obese children ages around 10 years old compare to normal weight showed that the zinc concentration was lower at obese children but not significantly different 22 .…”
Section: Discussionmentioning
confidence: 87%